Intensity-modulated proton therapy, volumetric-modulated arc therapy, and 3D conformal radiotherapy in anaplastic astrocytoma and glioblastomaIntensitätsmodulierte Protonentherapie, volumenmodulierte Arc-Therapie und dreidimensionale konformale Radiotherapie beim anaplastischen Astrozytom und Glioblastom - Adeberg, Sebastian; Harrabi, Semi B.; Bougatf, Nina; Bernhardt, Denise; Hörner-Rieber, Juliane; Körber, Stefan A.; Syed, Mustafa; Sprave, Tetyana; Mohr, Angela; Abdollahi, Amir; Haberer, Thomas; Herfarth, Klaus; et al. (Strahlentherapie und Onkologie, 2016)
PurposeThe prognosis for high-grade glioma (HGG) patients is poor; thus, treatment-related side effects need to be minimized to conserve quality of life and functionality. Advanced techniques such as proton radiation therapy (PRT) and volumetric-modulated arc therapy (VMAT) may potentially further reduce the frequency and severity of radiogenic impairment.Materials and methodsWe retrospectively assessed 12 HGG patients who had undergone postoperative intensity-modulated proton therapy (IMPT). VMAT and 3D conformal radiotherapy (3D-CRT) plans were generated and optimized for comparison after contouring crucial neuronal structures important for neurogenesis and neurocognitive function. Integral dose (ID), homogeneity index (HI), and inhomogeneity coefficient (IC) were calculated from dose statistics. Toxicity data were evaluated.ResultsTarget volume coverage was comparable for all three modalities. Compared to 3D-CRT and VMAT, PRT showed statistically significant reductions (p < 0.05) in mean dose to whole brain (−20.2 %, −22.7 %); supratentorial (−14.2 %, −20,8 %) and infratentorial (−91.0 %, −77.0 %) regions; brainstem (−67.6 %, −28.1 %); pituitary gland (−52.9 %, −52.5 %); contralateral hippocampus (−98.9 %, −98.7 %); and contralateral subventricular zone (−62.7 %, −66.7 %, respectively). Fatigue (91.7 %), radiation dermatitis (75.0 %), focal alopecia (100.0 %), nausea (41.7 %), cephalgia (58.3 %), and transient cerebral edema (16.7 %) were the most common acute toxicities.ConclusionEssential dose reduction while maintaining equal target volume coverage was observed using PRT, particularly in contralaterally located critical neuronal structures, areas of neurogenesis, and structures of neurocognitive functions. These findings were supported by preliminary clinical results confirming the safety and feasibility of PRT in HGG.